Measurement of the Ligand Field Spectra of Ferrous and Ferric Iron Chlorides Using 2p3d RIXS - Hahn, Anselm W; Van Kuiken, Benjamin E; Al Samarai, Mustafa; Atanasov, Mihail; Weyhermüller, Thomas; Cui, Yi-Tao; Miyawaki, Jun; Harada, Yoshihisa; Nicolaou, Alessandro; DeBeer, Serena (Inorganic chemistry, 2017)
Ligand field spectra provide direct information about the electronic structure of transition metal complexes. However, these spectra are difficult to measure by conventional optical techniques due to small cross sections for d-to-d transitions and instrumental limitations below 4000 cm . 2p3d resonant inelastic X-ray scattering (RIXS) is a second order process that utilizes dipole allowed 2p to 3d transitions to access d-d excited states. The measurement of ligand field excitation spectra by RIXS is demonstrated for a series of tetrahedral and octahedral Fe(II) and Fe(III) chlorides, which are denoted Fe(III)-T , Fe(II)-T , Fe(III)-O , and Fe(II)-O . The strong 2p spin-orbit coupling allows the measurement of spin forbidden transitions in RIXS spectroscopy. The Fe(III) spectra are dominated by transitions from the sextet ground state to quartet excited states, and the Fe(II) spectra contain transitions to triplet states in addition to the spin allowed Γ → Γ transition. Each experimental spectrum is simulated using a ligand field multiplet model to extract the ligand field splitting parameter 10Dq and the Racah parameters B and C. The 10Dq values for Fe(III)-T , Fe(II)-T , and Fe(III)-O are found to be -0.7, -0.32, and 1.47 eV, respectively. In the case of Fe(II)-O , a single 10Dq parameter cannot be assigned because Fe(II)-O is a coordination polymer exhibiting axially compressed Fe(II)Cl units. The T → E transition is split by the axial compression resulting in features at 0.51 and 0.88 eV. The present study forms the foundation for future applications of 2p3d RIXS to molecular iron sites in more complex systems, including iron-based catalysts and enzymes.